New bis-andrographolide ether from androgphis paniculata nees and evaluation of anti-HIV activity - Reddy, V. L. N.; Reddy, S. M.; Ravikanth, V.; Krishnaiah, P.; Goud, T. V.; Rao, T. P.; Ram, T. S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Venkateswarlu, Y (Natural Product Research, 2005)
Novel bis-andrographolide ether (1) and six known compounds andrographolide, 14-deoxy-11,12-didehydroandrographolide, andrograpanin, 14-deoxyandrographolide, (+/-)-5- hydroxy-7,8-dimethoxyflavanone, and 5-hydroxy-7,8-dimethoxyflavone have been isolated from the aerial parts of Andrographis paniculota and their structures were established by spectral data. All the isolates were tested for the anti-HIV and cytotoxic activity.
Keywords: Acanthaceae; Andrographis paniculata; anti-HIV; bis-andrographolide ether; Cytotoxic activity